2011
DOI: 10.1016/j.bcp.2011.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of human drug metabolites using fungal peroxygenases

Abstract: The synthesis of hydroxylated and O-or N-dealkylated human drug metabolites (HDMs) via selective monooxygenation remains a challenging task for synthetic organic chemists. Here we report that aromatic peroxygenases (APOs; EC 1.11.2.1) secreted by the agaric fungi 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 63 publications
(49 reference statements)
2
63
0
2
Order By: Relevance
“…Since its discovery 10 years ago, the potential use of UPO in applications ranging from chemical processes (including some relevant industrial transformations, such as alkane hydroxylation and olefin epoxidation) to the preparation of O-and N-dealkylated human drug metabolites, as well as bioremediation (polycyclic aromatic hydrocarbon [PAH] oxidation) and biosensor development, has been studied exhaustively (41)(42)(43)(44)(45)(46)(47)(48)(49)(50). For decades, regio-and enantioselective oxyfunctionalization has been a "forbidden territory" for most biocatalysts, except for P450 The stabilities of wt UPO1 (C) and the PaDa-I mutant (D) after incubation for 48 h in 50% organic cosolvents were assessed by incubating enzyme samples in 100 mM potassium phosphate buffer (pH 7.0) containing 50% (vol/vol) organic cosolvent in screw-cap vials.…”
Section: Y A[14]v R[15]g A[21]d Mutations)mentioning
confidence: 99%
“…Since its discovery 10 years ago, the potential use of UPO in applications ranging from chemical processes (including some relevant industrial transformations, such as alkane hydroxylation and olefin epoxidation) to the preparation of O-and N-dealkylated human drug metabolites, as well as bioremediation (polycyclic aromatic hydrocarbon [PAH] oxidation) and biosensor development, has been studied exhaustively (41)(42)(43)(44)(45)(46)(47)(48)(49)(50). For decades, regio-and enantioselective oxyfunctionalization has been a "forbidden territory" for most biocatalysts, except for P450 The stabilities of wt UPO1 (C) and the PaDa-I mutant (D) after incubation for 48 h in 50% organic cosolvents were assessed by incubating enzyme samples in 100 mM potassium phosphate buffer (pH 7.0) containing 50% (vol/vol) organic cosolvent in screw-cap vials.…”
Section: Y A[14]v R[15]g A[21]d Mutations)mentioning
confidence: 99%
“…UPOs have successfully been used as oxygenation tools for the synthesis of human drug metabolites 17, 18, 19. The first detailed studies on steroid hydroxylation by several UPOs revealed preferred accessibility of the hydrophobic C17 alkyl side chain to the substrate channel; the entrance of whole rings was found to be energetically penalized, in particular when the C3 position was already oxyfunctionalized 17, 20. ‐21 Consequently, substrates, such as testosterone, that lack an alkyl side chain or bearing oxidized C3 were not converted 20…”
Section: Introductionmentioning
confidence: 99%
“…As such, they are proving to be unusually efficient biocatalysts (27). Numerous drug compounds are efficiently oxidized to products that are often the same as those from mammalian CYP transformations (28). These properties have also afforded a rare and revealing opportunity to study the reaction steps in C−H bond hydroxylation events with a hemethiolate protein that is not a CYP, but which may function in analogous ways.…”
mentioning
confidence: 99%